Pengaturan Ulang Urutan Tata Letak Seri Antar Etalase - Hendy Tannady (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
Materials movement between facilities within space will be talking about the amount of costs to be incurred by the companies, many organizations do not realize the importance of the efficiency of material movement. Material handling cost is not only defined as all costs incurred to move material or human inter-facility, in vast perception,material movement can also be a movement of consumers who come to shop and between storefronts, it certainly raises the cost of time for consumers. This research discuss about redesigning the sequence of storefront layout in a shopping center. This research using Modified Spanning Tree method and result of this research is F2-F1-F7 F3-F4-F5-F6 for the optimum solution sequence.Keywords: Efficiency, Material Handling, Layout, Modified Spanning Tree